Cost-effectiveness of camrelizumab plus chemotherapy vs. chemotherapy in the first-line treatment of non-squamous NSCLC: Evidence from China - Dai, Hongbin; Wang, Wenyue; Fan, Xin; Chen, Yongfa (Frontiers in Medicine, 2023)
Objective We aimed to evaluate the cost-effectiveness of camrelizumab plus chemotherapy compared with chemotherapy alone as the first-line treatment for patients with metastatic or advanced non-squamous non-small cell lung cancer (NSCLC) without targetable epidermal growth factor receptor or anaplastic lymphoma kinase genetic aberrations in patients in China. Methods A partitioned survival model was constructed to estimate the cost-effectiveness of camrelizumab plus chemotherapy vs. chemotherapy in the first-line treatment of non-squamous NSCLC from a Chinese healthcare perspective. Survival analysis was performed to calculate the proportion of patients in each state using data from trial NCT03134872. The cost of drugs was obtained from Menet, and the cost of disease management was obtained from local hospitals. Health state data were obtained from published literature. Both deterministic sensitivity analyses (DSA) and probabilistic sensitivity analysis (PSA) were adopted to verify the robustness of the results. Results Compared with chemotherapy alone, camrelizumab plus chemotherapy provided 0.41 incremental quality-adjusted life years (QALYs) at an incremental cost of $10,482.12. Therefore, the incremental cost-effectiveness ratio of camrelizumab plus chemotherapy was $25,375.96/QALY from the Chinese healthcare perspective, much lower than three times the GDP per capita of China in 2021 ($35,936.09) as the willingness-to-pay threshold. The DSA indicated that the incremental cost-effectiveness ratio was most sensitive to the utility value of progression-free survival, followed by the cost of camrelizumab. The PSA illustrated that camrelizumab had 80% probability of being cost-effective at the threshold of $35,936.09 per QALY gained. Conclusion The results suggest that camrelizumab plus chemotherapy is a cost-effective choice in the first-line treatment for patients with non-squamous NSCLC in China. Although this study has limitations such as short time of use of camrelizumab, no adjustment of Kaplan–Meier curves and the median overall survival that has not been reached, the difference in results caused by these factors is relatively small.